Tanggungjawab Sosial dan Kinerja Keuangan pada Bank Umum Shariah di Indonesia - Ali Syukron (Dinar : Jurnal Prodi Ekonomi Syariah, 2018)
The purpose of this study was to examine the social performance of Islamic banking in Indonesia with its financial performance. Social performance appraisal method in this study using model of the Islamic Social Reporting Index which revealed 38 (thirty eight) social responsibility disclosure items, whereas for the assessment of financial performance from the aspects of profitability and liquidity, represented by the variable ROA, ROE, and FDR. The methodology of this study, including the type of descriptive analysis with a quantitative approach. The sampling technique was done by purposive sampling in order to obtain a representative sample in accordance with established criteria. The criteria used to determine the sample is the entire Islamic commercial banks recorded until 2012, publishes an annual report on the period 2007-2011, which publishes quarterly reports from the first quarter 2007 to fourth quarter 2012 and implement CSR in the period of 2007-2011.